Generalized Extended State Observer Based High Precision Attitude Control of Quadrotor Vehicles Subject to Wind Disturbance - Shi, Di; Wu, Zhong; Chou, Wusheng (IEEE access, 2018)
Wind disturbance may significantly degrade the attitude control performance during the flight of quadrotor vehicles. In order to meet the requirement of high-precision attitude control, a generalized extend state observer (GESO)-based disturbance and uncertainty estimation and attenuation control strategy is proposed in this paper. First, the disturbances are considered as a time polynomial function, and the {n} th order model of disturbances are augmented into the quadrotor dynamics. According to the reconstructed model, a GESO is designed and its stability is proved by the Lyapunov theory. Then, we analyze the influences of the observer order and bandwidth on the estimation accuracy in detail and give the gain tuning guidelines for GESO. Second, we design an attitude tracking controller based on the backstepping method and discuss the stability of the entire system. Finally, the numerical simulations and real-time experiments are carried out to evaluate the performance of the proposed controller with the GESO of different orders. Our results show that the proposed method can achieve precise attitude tracking for a quadrotor subject to wind disturbance. Furthermore, when the bandwidth of the GESO is fixed, the performance of the proposed controller improves with the increases of the GESO order.